Proximal and physicochemical characterization of fruits from promising avocado genotypes in three areas in the Dominican Republic - Alcántara-Marte, Yulisa; Tejada-Torres, José; Alcántara-De Tejada, Yanilka (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Characterization is one of the main factors to be considered for the use of any raw material to be industrialized and commercialized, and its quality depends on its origin. The objective of this research was to evaluate the fruit characteristics of promising avocado genotypes in the Dominican Republic, for which two studies were carried out. The first study evaluated the effect of genotype (Popenoe, Criollo, and Hass) and the second evaluated the effect of production area (north, central, and southeast Dominican Republic) on proximal (moisture, protein, lipid, and ash content) and physicochemical (titratable acidity, pH, water activity (aw), and soluble solids) characteristics of avocado pulp. Completely randomized designs with four replicates per study factor were performed. An analysis of variance was carried out, and Tukey's test was applied with a reliability of 95 %. The results show that fat, protein, and pH can vary according to genotype. Criollo avocados had lower fat content (6.40 %) and their protein percentage was statistically similar (p<0.05) to Hass and higher than Popenoe. The pH ranged from 5.96 (Criollo) to 6.98 (Hass). Production areas can influence the protein content, titratable acidity, and water activity (aw) in avocados. Those with the highest protein content are produced in the southeast, while those with the lowest acidity and highest water activity (aw) are produced in the central zone. These results corroborate the need to characterize genotypes and the origin of raw materials for industrialization and commercialization.